Left Ventricular Hypertrophy in Fabry's Disease in an Old Male Patient - Mohadese Firuzi; Hamid Khederlou; Narges Mohammadi (Publisher: Shahid Beheshti University of Medical Sciences)
Fabry disease is an X-linked disorder due to deficiency of the lysosomal hydrolasea-galactosidase A and the resultant accumulation of glycosphingolipids throughout the body, such as in the heart. Cardiac manifestations in Fabry disease are due to glycosphingolipid deposition in the myocardium, valves, and conduction system. Fabry cardiomyopathy, characterized by progressive severe concentric left ventricular hypertrophy. We, as a result of this, have reported a case of Fabry disease with left ventricular hypertrophy. He was admitted with dyspnea and also dizziness, general weakness, and acroparesthesias. Physical examination showed Angiokeratoma on the skin. The electrocardiography revealed ST-segment depression in leads V3–V6, and changes related to left ventricular hypertrophy. Echocardiography showed concentric left ventricular hypertrophy.